منظور النخب الجامعية للحرب الروسية الوكرانية - سارة بن زيان; زينب مختاري; د/ خضرون التواتي (جامعة عمار ثليجي الاغواط, 2024)
الملخص: هدف البحث إلى التعرف على منظور النخب للحرب الروسية الأوكرانية من خلال قناة الجزيرة، وتم استخدامالمنهج الوصفي، واستعان باستمارة على عينة بحثية قدرت ب 82 مفردة من الاساتذة الجامعيين على مستوى جامعة عمار ثليجيبالاغواط. وقدخلصتدراستناإلىمجموعةمنالنتائجكانأهمهاهوتخصيصالقناةحيزازمنيامعتبرالهاتهالحرب،كماوركزتعلىشقهاالتحليليوالعرضالمباشرللاخبار،وذلكماجعلإطارالصراعهوالغالبعلىهاتهالمعالجة،هذاوغابتعنهاالأهدافالإعلاميةالسلبيةوظهرالحيدفيالتحليلمنخلالاراءالفئةالمبحوثة،كلهاتهالأمورتشيرإلىأنالجزيرةشكلتوجهةنظربالنسبةللنخبللحربالروسيةالأوكرانية . الكلمات المفتاحية: منظور – النخب- الحرب الروسية الاوكرانية – قناة الجزيرة Abstract: The research aimed to identify the elites’ perspective on the Russian-Ukrainian war through Al Jazeera. The descriptive approach was used, and a questionnaire was used on a research sample estimated at 82 individuals from university professors at the level of Amar Thelidji University in Laghouat. Our study concluded with a set of results, the most important of which was that the channel allocated a significant amount of time to this war, and it also focused on its analytical part and the direct presentation of the news, and that is what made the conflict framework the dominant one in this treatment. Negative media objectives were absent from it, and neutrality appeared in the analysis through The opinions of the surveyed group: All of these things indicate that Al Jazeera formed the elites’ point of view regarding the Russian-Ukrainian war. Keywords: perspective - elites - the Russian-Ukrainian war - Al Jazeera
دراسة ميدانية على عينة من الاساتذة الجامعيين بجامعة عمار ثليجي الاغواط